Absorption and Resonance Rayleigh Scattering Spectra of Ag(I) and Erythrosin System and Their Analytical Application in Food Safety - Wang, Jian; Liu, Shaopu; Shen, Wei (Frontiers in Nutrition, 2022)
In pH 4.4~4.6 weakly acidic media, erythrosine (Ery) can react with Ag(I) to form hydrophobic ion-association complex, which can further aggregate to form nanoparticles with an average particle size of about 45 nm under the action of water phase extrusion and van der Waals force. As a result, it could lead to a decrease of absorbance, a significant enhancement of resonance Rayleigh scattering (RRS) and the appearance of a new emission spectrum. Based on these Phenomena, two new methods (spectrophotometry and RRS) were established for the determination of trace Ag(I). The detection limits for Ag(I) by spectrophotometry and RRS are 9.74 ng/ml and 0.12 ng/ml, respectively. In this paper, we have investigated the formation of nanoparticles, the optimum reaction conditions, the influence factors, explored the reason for enhancement of the scattering intensity and the effect of coexisting substance. This research shows that RRS method not only has good selectivity and high sensitivity, but also is simple and rapid. Analyzing of actual samples and standard samples, the determination result of this method is consistent with that of standard methods (Flame atomic absorption spectroscopy).